(untitled) - Avery, Peter (Oxford, 1998)
This book is a comprehensive introduction to teaching the pronunciation of North American Englissh. Part One contains an illustrated description of the sound system of English. Part Two provides ideas for overcoming common pronunciation problems. Part Three gives numerous useful classroom techniques. The book includes exercises, a glossary, and an index.
Keywords: English language,English language; Study and teaching,Pronunciation,Textbooks for foreign speakers